Applicability of thermal images and interpolation methods the examine the surface-temperature of compost prisms - Hunyadi, Gergely; Tamás, János (Acta Agraria Kaposváriensis, 2010)
Composting of sewage sludge is actually the most applicable waste treatment technology because the biological degradation gives us a final product which can be used as organic fertilizer in crop production.The utilization of the given compost depends on its maturity. The mostly used method to determine the maturity is temperature measurements. In this case they usually measure the inner temperature of the compost prism but the temperature of the surface is not analysed. The measurement of the surface-temperature next to the determination of the maturity may give the possibility to examine the homogeneity of the prism and analyse the biological processes in different points. The aim of this paper is the comparison of thermal images and potentiometric graphs made after on-sight measurements according to the density of the sampling points.
Keywords: composting; thermal images; interpolation; maturity